Developing self-learning skills in higher education in Vietnam: A survey of current practices and proposed solutions - Dao, Viet Hung; Nguyen, Mau Duc; Pham, Thi Hong Hanh (Nurture, 2025)
Purpose: This research explores how Vietnamese university students develop self-learning skills within traditional educational practices, focusing on fostering autonomy and lifelong learning in a student-centered environment. Design/Methodology/Approach: The study employs a mixed-methods approach. Quantitative data was collected through surveys, and qualitative data was gathered from interviews conducted with 508 student participants from six leading universities across Vietnam, representing a variety of academic disciplines. A 39-item questionnaire was used to measure opinions, experiences, and perceptions related to self-learning, utilizing a five-point Likert scale. Findings: The research shows that while Vietnamese students acknowledge the importance of self-learning, they face significant challenges due to the traditional teacher-centered educational model emphasizing rote learning. Key factors influencing self-learning include cognitive abilities, learning conditions, and the credit-based education system. Major pedagogical reforms are needed to foster an environment conducive to autonomous learning. Conclusion: The findings highlight the need for Vietnamese universities to adopt a more student-centered approach, enhance learning resources, and foster an inquiry-driven, autonomous learning culture. The development of comprehensive policies and institutional support is essential to create a conducive atmosphere for self-learning. Practical Implications: The study suggests that universities should focus on developing strategies and resources to promote student autonomy and independent learning. This includes the creation of policies and a supportive infrastructure to guide the transition toward more flexible and student-driven learning methods. Contribution to the Literature: This study highlights challenges in implementing self-learning in Vietnamese higher education and offers recommendations for reforms to align with global trends in autonomous learning.